LA RECHERCHE DES SALMONELLES DANS LES ELEVAGES DE POULET DE CHAIR DANS LA WILAYA DE MOSTAGANEM - KERSANI, Mansouria Wissam; BENNACEUR, Nesrine Fatima Zohra (My University, 2020)
The evolution of infectious diseases of food origin in the world and in particular in Algeria seems to be related to the presence of microorganisms in food and constitute nevertheless the problem of public health thus representing a source of human suffering. The present work deals with the estimation of the contamination of the poultry sector by Salmonella, one of the causes of bacterial food poisoning in Algeria and more particularly those with obligatory declaration. Since then, multi-resistant clones have emerged and their impact on human health in terms of morbidity and mortality has been documented. This work done in western Algeria in the wilaya of Mostaganem To carry out this study, several samples of broiler chickens were taken from a state breeding site in the wilaya of Mostaganem. and were tested for Salmonella contamination. The research carried out demonstrated the presence of salmonella in some samples, serotypes detected in broiler chickens are S.lindenburg, S. infantis, S.spp and for broiler chicks the identified serovar is: Salmonella enteritidis, the results showed resistance to antibiotics for the species which explains the uncontrolled use of antibiotics. The contamination of poultry farms by salmonella highlights the need to takemonitoring of the poultry sector, so to properly apply and respect the conditions andbreeding standards and good practice in health and hygiene safety.
Keywords: Poultry sector; Salmonella; Toxi-infection; Serotype; Antibiotic resistance.